Assessing the potential of seaweed extracts to improve vegetative, physiological and berry quality parameters in Vitis vinifera cv. Chardonnay under cool climatic conditions - Johan Yssel; Vicky Everaerts; Wendy Van Hemelrijk; Dany Bylemans; Mathabatha Evodia Setati; Bart Lievens; Erna Blancquaert; Sam Crauwels (PLoS ONE, 2025)
Seaweed extracts are promising plant biostimulants for viticulture, but their effects on white winegrape cultivars grown under cool climates remain fairly undocumented. Furthermore, information is limited on the biostimulant potential of some brown seaweed species like Ecklonia maxima. This study evaluated the impact of two commercial extracts (derived from Ascophyllum nodosum and Ecklonia maxima) on Vitis vinifera cv. Chardonnay in Belgium during the 2021 and 2022 growing seasons. The extracts, alongside a water‑control and an NPK‑reference (NPK‑Ref) treatment (with nitrogen, phosphorus, and potassium levels comparable to the extracts), were applied as foliar sprays five times at regular intervals, from flowering to ripening. In 2021 and 2022, A. nodosum significantly increased individual leaf area (+12% and +15%), while in 2021 A. nodosum‑treated vines had an increased chlorophyll content index (+12% CCI) and photosystem II (PSII) reaction centre density (+6%) relative to control vines. This corresponded with a small, but significant, improvement (+1.5%) in PSII maximum quantum yield (Fv∕Fm), whereas PSII electron transport efficiency (ΦE0) remained unchanged. Furthermore, increased berry size, mass, and sugar content were observed in A. nodosum‑treated vines during ripening in 2022, comparable to NPK‑Ref vines. Conversely, the E. maxima extract had limited effects on vegetative growth, physiology, and subsequent berry development. Yield increase from 2021 to 2022 varied by treatment, with a significant increase observed for E. maxima (+60%) and NPK‑Ref vines (+80%), relative to control vines. Our results indicate that seaweed extracts, specifically A. nodosum‑based, can enhance grapevine leaf area, CCI, and Fv∕Fm under cool climatic conditions. A. nodosum treatment was also associated with increased berry size and sugar content, while E. maxima treatment was associated with increased yield in the subsequent, warmer season. Altogether, our study highlights that the differential effects of seaweed extracts on grapevine development are modulated by species and environmental conditions.